Dexamethasone during pregnancy impairs maternal pancreatic β-cell renewal during lactation. Issue 2 (February 2019) - Teixeira, Caio Jordão; Santos-Silva, Junia Carolina; de Souza, Dailson Nogueira; Rafacho, Alex; Anhe, Gabriel Forato; Bordin, Silvana
Abstract : Pancreatic islets from pregnant rats develop a transitory increase in the pancreatic β-cell proliferation rate and mass. Increased apoptosis during early lactation contributes to the rapid reversal of those morphological changes. Exposure to synthetic glucocorticoids during pregnancy has been previously reported to impair insulin secretion, but its impacts on pancreatic islet morphological changes during pregnancy and lactation have not been described. To address this issue, we assessed the morphological and molecular characteristics of pancreatic islets from rats that underwent undisturbed pregnancy (CTL) or were treated with dexamethasone between the 14th and 19th days of pregnancy (DEX). Pancreatic islets were analyzed on the 20th day of pregnancy (P20) and on the 3rd, 8th, 14th and 21st days of lactation (L3, L8, L14 and L21, respectively). Pancreatic islets from CTL rats exhibited transitory increases in cellular proliferation and pancreatic β-cell mass at P20, which were reversed at L3, when a transitory increase in apoptosis was observed. This was followed by the appearance of morphological features of pancreatic islet neogenesis at L8. Islets from DEX rats did not demonstrate an increase in apoptosis at L3, which coincided with an increase in the expression of M2 macrophage markers relative to M1 macrophage and T lymphocyte markers. Islets from DEX rats also did not exhibit the morphological characteristics of pancreatic islet neogenesis at L8. Our data demonstrate that maternal pancreatic islets undergo a renewal process during lactation that is impaired by exposure to DEX during pregnancy.